The Grammatical Role in Coloring Ideas in Artistic Prose - Al-Fayadh, Hanan (Dirasat: Human and Social Sciences, 2021)
This research aims to identify grammatical role in enabling the writer to move artfully from an idea to another within the text, without resorting to defective repetition. It traces the term "beginning" and the corresponding terminology in the ancient Arab criticism, and shows how the Arab critics paid great attention to it, given the role it plays in literary text, then reveals a different way of dealing with this term as an introduction to every main idea in the text, not limited to the beginnings of the text. It dealt with examples of artistic prose of three writers known for the excellence of their literary style and uniqueness of their output and its quality, so that their prose production is considered poetic prose. These writers are: Al-Manfalouti, Al-Rafi’i and Jobran. What is meant by "beginning" here is what constitutes a complete meaning, whether it comes from one sentence or more. The research concluded that there are several grammatical methods in the entries of the main ideas in the texts under study by the three writers, which formed pillars upon which these texts were based, including: appeal, condition, emphasis with letters of meanings, repetition in multiple forms, question, exclamation, negation. The research clarified the significance and effect of each style or syntactic combination on the initiation of the ideas of the text, as the author’s use of this method or that composition was not random, but rather it was selected due to the uniqueness of this style in its position.